Categorias Existenciais (Coimbra University Press, 2025)
What is at stake in all these studies are the existential categories. These are revealed in their vital execution, so that the diversity of points of view may be more useful to put the reader on the trail of existential categories than a text about them, in which they would run the risk of becoming categories of thought. For this reason, this volume welcomes with the same interest studies on The Phenomenology of Spirit and Céline, on the phenomenon of desire, in the Phaedo, and the “for the sake of” in the existential analysis of Dasein, by Heidegger, the phenomenon of the grotesque, in Flannery O'Connor’s work, and the subject of “I would prefer not to”, in Bartleby.